Temporal localization of osteocalcin protein during healing of tooth extraction sockets in rats. - Rodrigues Luvizuto, E.; Mônica Dias, S.; Chiantelli Cláudio-Coutinho, C.; Alves Machado, L.; Rangel Garcia-Júnior, I.; Okamoto, T.; Okamoto, Roberta [UNESP] (My University, 2010)
The aim of this study was to evaluate the expression of osteocalcin protein during the alveolar bone healing process in rats. Twenty four rats were used in this study and, after anesthetic induction, they had their right upper incisors extracted. At 7, 14, 21 and 28 days after the tooth extraction, the animals were injected 4% formaldehyde. The histological tissue pieces were colored in hematoxilin and eosin and the immunohistochemistry reaction for osteocalcin was performed. At seven days lesser neoformed trabeculae bone and a small quantity of osteocalcin labeling were observed. At 14 and 21 days a larger quantity of neoformed trabeculae bone and higher osteocalcin values were detected. At 28 days the largest quantity of neoformed trabeculae bone and a decrease on the amount of osteocalcin immunolabelling were noticed. According to our results and considering the limits of the present study it is possible to conclude that a greater osteocalcin expression is observed at 14 and 21 days postoperatively, characterizing the periods when intense mineralization of the bone tissue occurs during the alveolar bone healing process.
Keywords: osteocalcin; animal; chemistry; male; rat; time; tooth extraction; tooth socket; Wistar rat; wound healing; Animals; Male; Osteocalcin; Rats; Rats, Wistar; Time Factors; Tooth Extraction; Tooth Socket; Wound Healing